Thrombosis related to true axillo-brachial arterial aneurysm following ligation of longstanding arteriovenous fistula for hemodialysis - Tsutomu Doita, MD; Taro Yamasumi, MD; Takashi Nakamura, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
A 52-year-old man who had received hemodialysis via a left radial–cephalic arteriovenous fistula (AVF) for 18 years presented with severe ischemic symptoms in the left upper arm 12 years after occlusion of the AVF. Diagnostic imaging revealed thrombotic occlusion from a left axillary–brachial artery aneurysm, which required distal bypass surgery. The inflow artery of an AVF can develop aneurysmal degeneration, resulting in upper limb ischemia by embolization or decreased flow, especially with a ligated or occluded AVF or immunosuppressive therapy after renal transplantation. In such cases, the AVF should be monitored, even if ligated or occluded.